2022
DOI: 10.1111/sltb.12825
|View full text |Cite
|
Sign up to set email alerts
|

Roles of alcohol use disorder and resilience in risk of suicide attempt in men: A Swedish population‐based cohort

Abstract: Introduction: Alcohol use disorder (AUD) has been identified as a strong risk factor for suicide attempt. However, few studies have considered protective factors that may moderate this association, such as resilience. Methods:We used longitudinal nationwide Swedish data of 903,333 males born 1960-1980 and 48,285 males born 1949-1951. We performed Cox proportional hazards models to test the role of AUD, resilience, and their interaction on risk for suicide attempt. We used co-relative models to account for fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 45 publications
(83 reference statements)
1
15
0
Order By: Relevance
“…Our search strategy initially yielded 29 533 records; after removal of duplicates, 16 347 remained ( Figure 1 ). After abstract screening and full-text review, 19 studies 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 identified from the search strategy and 5 studies 53 , 54 , 55 , 56 , 57 identified from manual reviews were included for analysis, for a total of 24 studies with 37 870 699 participants (59.7% male and 40.3% female) ( Table 2 ). Participants ranged in age from 15 years to 65 years or older.…”
Section: Resultsmentioning
confidence: 99%
“…Our search strategy initially yielded 29 533 records; after removal of duplicates, 16 347 remained ( Figure 1 ). After abstract screening and full-text review, 19 studies 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 identified from the search strategy and 5 studies 53 , 54 , 55 , 56 , 57 identified from manual reviews were included for analysis, for a total of 24 studies with 37 870 699 participants (59.7% male and 40.3% female) ( Table 2 ). Participants ranged in age from 15 years to 65 years or older.…”
Section: Resultsmentioning
confidence: 99%
“…Our secondary aim was to investigate the association of specific domains of alcohol use with these outcomes, to better understand the potential mechanisms linking alcohol use and suicidal behaviour. Alcohol use disorder and suicidal behaviour are both associated with distinct gender 11 , 20 and age differences, 21 and we therefore sought to determine whether the association between alcohol use and suicidal behaviour also reflected these differences.…”
Section: Aimsmentioning
confidence: 99%
“… 9 Recent studies of this association indicate that there are likely potential causal mechanisms between alcohol use disorders and suicidal behaviour, even after accounting for genetic and familial environmental confounding. 10 , 11 It is not clear, however, if increasingly harmful alcohol use and alcohol-related behaviours across the general population show proportionate associations with suicidal behaviour. Only one study 12 to date looked at an association between increasingly harmful alcohol use and suicidal behaviour in an adult general population sample.…”
mentioning
confidence: 99%
“…Suicidal behavior has long been studied in the context of psychiatric illness and is particularly associated with substance use disorders, personality disorders and depression [1,2]. The associations between substance use disorders and suicidal behavior have been reported in many studies [3][4][5][6], with evidence of a possible causal pathway from alcohol use disorder (AUD) to suicide attempt and death [7][8][9].…”
Section: Introductionmentioning
confidence: 99%